Politicizing science funding undermines public trust in science, academic freedom, and the unbiased generation of knowledge - Efimov, Igor R.; Flier, Jeffrey S.; George, Robert P.; Krylov, Anna I.; Maroja, Luana S.; Schaletzky, Julia; Tanzman, Jay; Thompson, Abigail (Frontiers in Research Metrics and Analytics, 2024)
This commentary documents how federal funding agencies are changing the criteria by which they distribute taxpayer money intended for scientific research. Increasingly, STEMM (Science, Technology, Engineering, Mathematics, and Medicine) funding agencies are requiring applicants for funding to include a plan to advance DEI ("Diversity, Equity, and Inclusion") in their proposals and to dedicate a part of the research budget to its implementation. These mandates undermine the academic freedom of researchers and the unbiased generation of knowledge needed for a well-functioning democracy. Maintaining excellence in science is fundamental to the continuation of the U.S. as a global economic leader. Science provides a basis for solving important global challenges such as security, energy, climate, and health. Diverting funding from science into activities unrelated to the production of knowledge undermines science's ability to serve humankind. When funding agencies politicize science by using their power to further a particular ideological agenda, they contribute to public mistrust in science. Hijacking science funding to promote DEI is thus a threat to our society.